L’amore nei paesi musulmani: un percorso di comprensione - Spreafico, Andrea (SocietàMutamentoPolitica, 2012)
This critical note proposes a review of the Fatema Mernissi’s book dealing with love in North African Arabian societies. The Moroccan sociologist outlines a picture about feelings of love, seduction, beauty and marriage in the Islamic context, using several sources: historical, literary, religious, philosophical, interviews, observations, content analysis of websites, memories and personal reflections. The result is a work that can be useful in order to undertake a path of mutual understanding between individuals referring to different constellations of cultural elements.